No Viral Transcripts Associated with Folliculotropic Mycosis Fungoides Using a High Throughput Sequencing Approach - Aurélie Du-Thanh; Olivier Dereure; Justine Cheval; Marine Dumarest; Liza Al-Shikhley; Céline Girard; Bernard Guillot; Marc Eloit (Medical Journals Sweden, 2017)
Abstract is missing (Short communication)